HARTĂ - HÂRTIE - CARTE: NUANȚĂRI SEMANTICE PENTRU DEZVOLTAREA REPERTORIULUI PLURILINGV ȘI PLURICULTURAL AL STUDENȚILOR STRĂINI CARE ÎNVAȚĂ LIMBA ROMÂNĂ CA L2. - DINCĂ, Irina (Studii de Ştiintă şi Cultură, 2023)
The present approach proposes an experiment for the development of the plurilingual and pluricultural repertoire of foreign students learning Romanian as a second language, speakers of Arabic, Bengali, Hebrew, English, French, German, Greek, Italian, Persian, Portuguese, Spanish, Turkish or Turkmen. Regarding the methodological resources, they include dictionaries and etymology studies, also considering the recommendations from the Complementary Volume with New Descriptors (2020), which develop the descriptors from the Common European Framework of Reference for Languages (2001). In the analytical part, the research followed the association in multilingual networks of some Romanian words with others similar in form or meaning from the languages the students know. Starting from the etymologies of the selected words, we also decoded the phonetic, semantic and sociocultural nuances that differentiate them, to avoid confusion and misunderstandings.